PROGRAM LOYALITAS DENGAN A CARD FLAZZ PADA MINIMARKET ALFAMART - KUSWADI, FILICIUS GORBI (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The competition among the retailers cause retailers build customer loyalty. One of the way to build it is by applied loyalty program. The loyalty program have the influenced towards the relationship between retailer and customer. The main question is identify the type-type of loyalty program that given Alfamart Minimarket, and identify the impact of loyalty program toward customer loyalty at Alfamart Minimarket. There are the various loyalty program for customer, and its showing that the retailer care to customers. By the memberships cards can build the retailer community. The interesting rewards to customer can build the positive respond. The succesfully Alfamart to reach the Superbrand award at 2010, 2011, and 2012 proved that the loyalty program have influenced towards image and implied towards the buying behavior.